ChemInform Abstract: Polymethine Dyes in Hybrid Photovoltaics: Structure—Properties Relationships. Issue 26 (June 2016) - Saccone, Davide; Galliano, Simone; Barbero, Nadia; Quagliotto, Pierluigi; Viscardi, Guido; Barolo, Claudia
Abstract: Review: summary of design strategies, the main synthetic routes, and the optical and photovoltaic properties of cyanine and squaraine sensitizers applied in photovoltaics; 146 refs.